2014
DOI: 10.1098/rspb.2013.2528
|View full text |Cite
|
Sign up to set email alerts
|

Multiple transgressions of Wallace's Line explain diversity of flightlessTrigonopterusweevils on Bali

Abstract: The fauna of Bali, situated immediately west of Wallace's Line, is supposedly of recent Javanese origin and characterized by low levels of endemicity. In flightless Trigonopterus weevils, however, we find 100% endemism for the eight species here reported for Bali. Phylogeographic analyses show extensive in situ differentiation, including a local radiation of five species. A comprehensive molecular phylogeny and ancestral area reconstruction of Indo-Malayan-Melanesian species reveals a complex colonization patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 56 publications
(66 reference statements)
4
58
1
Order By: Relevance
“…In contrast, the second set of calibrations implies a colonization during the early Miocene when both the Sunda and Sahul regions collided (Seton et al ., ). This geological rearrangement resulted in a massive orogeny in Wallacea (Hall, , ) and Melanesia (Toussaint et al ., ) responsible for the exchange of biotas between the Oriental and Australian regions (Tänzler et al ., ; Toussaint et al ., ; Condamine et al ., ). Hence, these contrasting results imply either a climatic or a geological factor to explain the biogeographic history of Nicrophorus in Southeast Asia. The biogeographic reconstruction based on the first calibration set recovers four Neotropical colonization events in the last 4 Myr (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the second set of calibrations implies a colonization during the early Miocene when both the Sunda and Sahul regions collided (Seton et al ., ). This geological rearrangement resulted in a massive orogeny in Wallacea (Hall, , ) and Melanesia (Toussaint et al ., ) responsible for the exchange of biotas between the Oriental and Australian regions (Tänzler et al ., ; Toussaint et al ., ; Condamine et al ., ). Hence, these contrasting results imply either a climatic or a geological factor to explain the biogeographic history of Nicrophorus in Southeast Asia. The biogeographic reconstruction based on the first calibration set recovers four Neotropical colonization events in the last 4 Myr (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on a few flightless weevils have suggested that they have been able to colonize numerous remote archipelagos and islands likely due to their long and complex histories in the regions (Claridge et al, 2017;Machado et al, 2017;T€ anzler et al, 2016). However, the mechanism and transporting vectors of effective long-distance dispersal across oceanic barriers remain elusive for these weevils.…”
Section: Probable Mechanisms Of Overwater Dispersal Of Remote Oceanmentioning
confidence: 99%
“…flightless Trigonopterus weevils in Bali, T€ anzler, Toussaint, Suhardjono, Balke, & Riedel, 2014). Conservation of insular species and endangered populations in their peripheral ranges is crucial for preserving rare alleles and unique phenotypes.…”
Section: Cryptic Species Diversity and Conservation Of Island Endemicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, only about 30% of bird, reptile, amphibian, butterfly and snail species are distinct to one side or another of Lombok Strait (Mayr, ). The majority of taxa are shared by Lombok and Bali, and phylogeographic data demonstrate some plants and animals have experienced numerous exchanges of individuals across Lombok Strait (e.g., Tänzler, Toussaint, Suhardjono, Balke, & Riedel, ; Thomas et al., ). Even well‐recognized features such as Wallace's line involve a mixture of ecological and evolutionary processes in their maintenance (e.g., Condamine et al., ).…”
Section: Introductionmentioning
confidence: 99%